Klasifikasi ABC Hybrid Berdasarkan Space Requirement dan Peak Value untuk Prioritas Persediaan: Hybrid ABC Classification Based on Space Requirement and Peak Value for Inventory Prioritization - Sasmito, Mikhael Kevin; Santoso, Amelia (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2026)
Abstract— Warehouses play a crucial role in the supply chain by providing storage for raw materials, work-in-process, and finished goods to support smooth production operations. The increasing number and diversity of stock keeping units (SKUs) require companies to adopt an inventory classification method capable of prioritizing inventory management more comprehensively. Conventional ABC classification typically relies on a single criterion, making it insufficient to fully represent the diverse characteristics of SKUs. This study aims to implement a hybrid ABC classification based on two criteria, namely space requirement and peak value, in the warehouse of PT XYZ. A quantitative case study approach was employed using production target data, the Bill of Materials (BOM), packaging dimensions, and inventory value. Peak demand was first determined based on the maximum production target and then converted into peak packs, which served as the basis for calculating space requirement and peak value. Each criterion was independently classified using ABC analysis and subsequently integrated through a priority score to generate the hybrid ABC classification. The results indicate that the proposed hybrid ABC approach effectively classifies SKUs by simultaneously considering storage space requirements and inventory value, thereby providing a more comprehensive inventory prioritization than the conventional single-criterion ABC classification. The resulting classification can serve as a decision-support tool for inventory management in warehouses and provide a foundation for future research on storage systems and warehouse management. Keywords: Hybrid ABC classification; space requirement; peak value; inventory management; warehouse Abstrak—Warehouse merupakan salah satu elemen penting dalam supply chain yang berfungsi sebagai tempat penyimpanan bahan baku, barang setengah jadi, dan barang jadi untuk mendukung kelancaran aktivitas produksi. Meningkatnya jumlah dan keragaman stock keeping unit (SKU) menyebabkan perusahaan memerlukan metode klasifikasi persediaan yang mampu menentukan prioritas pengelolaan secara lebih komprehensif. Klasifikasi ABC konvensional umumnya hanya menggunakan satu kriteria sehingga belum mampu merepresentasikan karakteristik SKU secara menyeluruh. Penelitian ini bertujuan menerapkan klasifikasi ABC Hybrid menggunakan dua kriteria, yaitu space requirement dan peak value, pada warehouse PT XYZ. Penelitian menggunakan pendekatan kuantitatif dengan studi kasus berdasarkan data target produksi, Bill of Material (BOM), dimensi packaging, dan nilai persediaan. Nilai peak demand dihitung berdasarkan target produksi maksimum, kemudian dikonversi menjadi peak packs sebagai dasar perhitungan space requirement dan peak value. Masing-masing kriteria diklasifikasikan menggunakan analisis ABC, kemudian diintegrasikan melalui priority score untuk menghasilkan klasifikasi ABC Hybrid. Hasil penelitian menunjukkan bahwa pendekatan ABC Hybrid mampu mengelompokkan SKU berdasarkan kebutuhan ruang penyimpanan dan nilai ekonominya secara simultan sehingga memberikan prioritas pengelolaan persediaan yang lebih komprehensif dibandingkan klasifikasi ABC satu kriteria. Hasil klasifikasi ini diharapkan dapat menjadi dasar dalam pengambilan keputusan pengelolaan persediaan pada warehouse serta mendukung penelitian lanjutan yang berkaitan dengan sistem penyimpanan dan manajemen warehouse. Kata kunci: klasifikasi ABC Hybrid; space requirement; peak value; manajemen persediaan; warehouse